Penggunaan Bahasa Indonesia Di Media Sosial Facebook - Ibyan Zaenul Haq; Aria Perbawa (Simpati, 2023)
The purpose of this article is to fulfill our task. Regarding the use of Indonesian on social media on Facebook, messages have increased in recent years, and we researched the use of Indonesian on social media on Facebook, in this study, we analyzed the use of Indonesian on Facebook by using text and data analysis methods of public user accounts. We found that the use of Indonesian on Facebook tends to be informal and contains elements of slang, such as OTW, Baper, Gaje, Santuy, and SKSD. In addition, the use of words in English is also very common in the use of Indonesian on Facebook, besides that many also use regional languages, and the use of social media on Facebook is also used by many people who sell online. The use of Indonesian on Facebook also shows interest. high emotional. Negative influences also arise such as the spread of fake news information and the use of impolite and unethical language. And also positive influences such as the use of which is more concise and efficient to use.